CFSP: The capability-expectation gap revisited. A data-based analysis - Annegret Bendiek; Minna Ålander; Paul Bochtler (Stiftung Wissenschaft und Politik (SWP), 2020)
The global political situation in Europe's neighbourhood has deteriorated dramatically in recent years, and this has had significant consequences for the European Union (EU). Conflicts are multiplying in Eastern Europe and in the Mediterranean Sea; Russia and China are showing increasingly expansive tendencies in South Eastern Europe; and the USA is becoming less and less reliable as a security provider for Europe. Against this background, it is striking that the Common Foreign and Security Policy (CFSP) still falls far short of what would be expected from the EU given the size of its internal market. The unanimity principle in the Council of the EU is often blamed for this. However, an analysis of CFSP data shows that the Member States are clearly satisfied with symbolic policy measures, despite their political rhetoric. This situation will not be resolved either by introducing simple majority voting or with mere declarations of political will from governments. The dialogue on the future of Europe should be seen as an opportunity to remedy the inability to act in the field of foreign policy by harmonising the CFSP.
Keywords: 320